Modeling the Predictive Value of Pain Intensity on Costs and Resources Utilization in Patients With Peripheral Neuropathic Pain. Issue 3 (March 2015) - Pérez, Concepción; Navarro, Ana; Saldaña, María T.; Wilson, Koo; Rejas, Javier
<x xml:space="preserve">Abstract</x> Objective: The aim of the present analysis was to model the association and predictive value of pain intensity on cost and resource utilization in patients with chronic peripheral neuropathic pain (PNP) treated in routine clinical practice settings in Spain. Methods: We performed a secondary economic analysis based on data from a multicenter, observational, and prospective cost-of-illness study in patients with chronic PNP that is refractory to prior treatment. Pain intensity was measured using the Short-Form McGill Pain Questionnaire. Univariate and multivariate linear regression models were fitted to identify independent predictors of cost and health care/non–health care resource utilization. Results: A total of 1703 patients were included in the current analysis. Pain intensity was an independent predictor of total costs ([total costs]=35.6 [pain intensity]+214.5; coefficient of determination [R2]=0.19, P<0.001), direct costs ([direct costs]=10.8 [pain intensity]+257.7; R2=0.06, P<0.001), and indirect costs ([indirect costs]=24.8 [pain intensity]−43.4; R2=0.20, P<0.001) related to chronic PNP in the univariate analysis. Pain intensity remains significantly associated with total costs, direct costs, and indirect costs after adjustment by other covariates in the multivariate analysis (P<0.001). None of the other variables considered in the multivariate analysis were predictors of resource utilization. Discussion: Pain intensity predicts the health care and non–health care resource utilization, and costs related to chronic PNP. Management of patients with drugs associated with a higher reduction of pain intensity may have a greater impact on the economic burden of that condition.